2020
DOI: 10.1002/jmv.25920
|View full text |Cite
|
Sign up to set email alerts
|

Potential of live pathogen vaccines for defeating the COVID‐19 pandemic: History and mechanism

Abstract: The whole world has entered a terrible crisis with a huge and increasing amount of human deaths and economic loss in fighting the pandemic of COVID-19 caused by the novel coronavirus termed SARS-CoV-2. The live pathogen vaccine (LPV) strategy, which originated in ancient China for fighting smallpox, has been applied successfully in the USA military recruits for decades to control acute respiratory diseases caused by types 4 and 7 adenoviruses. This strategy has also been widely employed in veterinary medicine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 35 publications
(60 reference statements)
0
33
0
Order By: Relevance
“…The development of live attenuated vaccines requires the organism to be modified via passage multiple times under unique conditions in the laboratory until it loses enough key virulent factors so as to not cause disease, but retains its ability to replicate in the vaccine recipient, and stimulate a robust immune response that protects against infection ( 84 86 ). These vaccines tend to be highly immunogenic, do not require an adjuvant and provide long-lasting immunity.…”
Section: Different Vaccine Approaches Used In Covid-19 Vaccine Develomentioning
confidence: 99%
See 1 more Smart Citation
“…The development of live attenuated vaccines requires the organism to be modified via passage multiple times under unique conditions in the laboratory until it loses enough key virulent factors so as to not cause disease, but retains its ability to replicate in the vaccine recipient, and stimulate a robust immune response that protects against infection ( 84 86 ). These vaccines tend to be highly immunogenic, do not require an adjuvant and provide long-lasting immunity.…”
Section: Different Vaccine Approaches Used In Covid-19 Vaccine Develomentioning
confidence: 99%
“…Reverse genetics can be employed for the rational design of the ideal attenuated SARS-CoV-2 vaccine virus, for example by determining key virulence factors, as has been done for other coronaviruses ( 87 ). Long-term maintenance of consistent live vaccine stocks is also problematic ( 85 , 86 ). Despite the challenges, three codon-pair deoptimized live attenuated vaccines are currently undergoing pre-clinical testing, but none have yet progressed to clinical trials ( 7 ) ( Table 1 ).…”
Section: Different Vaccine Approaches Used In Covid-19 Vaccine Develomentioning
confidence: 99%
“…Second, the coronavirus could prevent seepage from the immunity developed by these vaccines through quick progression. Thus, the manufacturer should be aware and careful during the development of these (inactivated and live attenuated) vaccines against SARS-CoV-2 [ 71 ].…”
Section: Strategies To Develop a Vaccine Against Sars-cov-2mentioning
confidence: 99%
“…10 Therefore, it is of great significance to develop whole-virus vaccines, particularly live vaccines which are usually more efficacious and less costly than other vaccines, for COVID-19. 11 Currently, several inactivated vaccines for COVID-19 have entered clinical trials, 8,9 but progress of live vaccine development for COVID-19 has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%